Comparison of Domestic and Foreign Safety Standards for Edible Vegetable Oils（Ⅱ） ——Physicochemical Indicators - ZHAO Chen-wei; JIN Qing-zhe; WANG Xing-guo (Liang you shipin ke-ji)
This article systematically compared the differences in physicochemical indicators such as acid value, peroxide value, solvent residue, free gossypol, and frying oil discard points between China and international organizations, countries and regions such as the Codex Alimentarius Commission, the European Union, the United States, Japan, Australia and New Zealand, Singapore, India, South Korea and Russia in terms of safety standards for edible vegetable oils. The study found that: in terms of acid value, only China, CAC, India, and Russia have stipulated the acid value for crude oil, and China’s acid value indicators for edible vegetable oils are basically consistent with foreign standards. In terms of peroxide value, only China has stipulated the peroxide value for crude oil, and China’s peroxide value indicators for edible vegetable oils are higher than foreign standards. In terms of solvent residue, only China, CAC, the EU, Singapore, India and South Korea have made provisions, with Chinese limits being higher than foreign standards. In terms of gossypol, only China has made provisions and in terms of polar components, Chinese limit values are higher than foreign standards. It is suggested that the limits of peroxide value, solvent residue, gossypol and polar components should be adjusted in the revision of national safety standards for edible vegetable oils in China.